Cité et réciprocité, City and Reciprocity : The Role of Cultural Beliefs in the Roman Economy - Verboven, Koenraad (Annales. Histoire, Sciences Sociales, 2012)
La nouvelle économie institutionnelle est devenue populaire dans la recherche de l’économie antique depuis une dizaine d’années. Pourtant la notion de « croyances culturelles », qui joue un rôle central dans l’œuvre de Douglass North et dans les analyses du changement institutionnel par Avner Greif, a été largement ignorée. J’affirme qu’une approche néo-institutionnelle qui utilise cette notion de « croyances culturelles » offre une meilleure voie pour comprendre l’influence des idéologies et des valeurs morales sur l’économie antique que le modèle de Moses Finley. Des croyances culturelles ne sont pas des contraintes déterministes sur le comportement humain, mais elles aident à orienter les prises de décision et permettent d’anticiper les (ré) actions des autres. J’étudie deux ensembles de normes et de valeurs qui, dans la culture romaine, ont profondément marqué le cadre institutionnel de l’économie. L’un était centré sur la réciprocité. Ses normes et valeurs ont permis de construire et de maintenir des réseaux sociaux au-delà du groupe de la familia étendue avec ses affranchis. Elles étaient à la base du développement de la loi des obligations et de la représentation. L’autre se fondait sur la cité. Il a formé la culture politique en créant des droits et des obligations personnelles et en imposant des demandes légitimes aux élites politiques de défendre ceux-ci et de garantir et de stimuler des intérêts privés et communs. Le droit romain et la justice étaient ses résultats les plus importants. Idéologiquement, l’Empire romain se présentait comme une méta-cité qui incorporait les communautés locales qui, à leur tour, étaient graduellement transformées sur le modèle de la cité. Ces deux ensembles de croyances culturelles ont baissé les coûts de transactions, mais ils n’ont jamais menacé la prééminence de l’aristocratie locale et impériale. Vers la fin du IIe siècle de notre ère, les cités locales se sont affaiblies tandis que l’administration impériale se renforçait. Les aristocraties locales et régionales se sont tournées vers la bureaucratie et l’armée impériales pour maintenir leur rang social, leur influence et leur pouvoir. L’idéologie de la cité comme principe dominant de la culture politique devenait soumise à celle de l’empereur sacral, garant de la justice et de l’ordre divins. EN: New Institutional Economics have become popular in ancient economic history research the past decade. However, the notion of “cultural beliefs” that plays a central role in Douglass North’s recent work and in Avner Greif’s analysis of institutional change, has been largely ignored. I argue that a neo-institutional “cultural beliefs approach” offers a better way to understand the influence of ideology and moral values on the ancient economy than the Finley model does. Cultural beliefs are no deterministic constraints on human behavior but help to orient decision making and allow anticipating the (re)actions of others. I explore two key sets of norms and values in Roman culture that profoundly marked the economy’s institutional framework. One centered on reciprocity. Its norms and values supported social networks beyond the confines of the familia-freedmen group and underlay the development of contract and agency law. Another set rested on citizenship. It shaped political culture by creating individual rights and obligations and laying legitimate claims on political elites to enforce these and to take action to secure and stimulate private and common interests. Roman law and the distribution of justice was its prime off-spring. Ideologically the Roman Empire presented itself as a meta-city that incorporated local communities which in turn were gradually transformed to fit the civitas model. Both belief sets lowered transaction costs, but they never threatened the preeminent position of local and imperial aristocracies. Towards the end of the second century CE local communities became weaker while the imperial administration grew stronger. This caused local and regional aristocracies to turn to the imperial court and army for status, influence and power. The ideology of citizenship as the guiding principle of political culture gave way to that of the sacred emperor who guaranteed divine justice and order.
Keywords: Roman Empire; ancient economic history; ancient economies; cultural beliefs approach; institutional economics

La subsistance de l'homme. La place de l'économie dans l'histoire et la société - Praquin, Nicolas (Comptabilité Contrôle Audit, 2012)
Keywords: La subsistance de l'homme: La place de l'économie dans l'histoire et la société (Book); POLANYI, Karl, 1886-1964; The Livelihood of Man; book review; economic development; nonfiction

Les sociétés civiles entre risques ploutocratiques de la philanthropie et alternatives solidaires : une lecture polanyienne, The civil societies between the plutocratic risks of philanthropy and solidarity based alternatives : a Polanyian reading - Servet, Jean-Michel (Mondes en développement, 2012)
Tant dans les pays du Nord que dans ceux du Sud, un compromis entre une logique néo-libérale anti-étatiste et certains intérêts des organisations non gouvernementales a marqué la construction des sociétés civiles. Il s’est réalisé notamment à travers le social business soutenu par de grandes entreprises. En mobilisant le concept polanyien de principe d’intégration économique, l’analyse a pour ambition de comprendre les limites de ce nouveau modèle de philanthropie et ce qui le différencie de l’économie solidaire., Both in the Norths and in the Souths, a compromise between a neoliberal anti-statist logic and interests of non governmental organizations marked the construction of civil societies. This is achieved particularly through the social business supported by big companies. By mobilizing the polanyien concept of principle of economic integration, the analysis aims to understand the limits of this new model of philanthropy and what differentiates it of the solidarity based economy.
Keywords: NGOs; Polanyi; formal and informal sectors; institutional arrangements; nonprofit institutions; political processes: rent-seeking, lobbying, elections, legislatures, and voting behavior; principes d'intégration économique; shadow economy; social business; économie solidaire

L'idéologie marchande au service de la biodiversité ? - Tordjman, Hélène; Boisvert, Valérie (Mouvements, 2012)
Keywords: biodiversity; markets

Retour sur le désencastrement - Brisset, Nicolas (Revue européenne des sciences sociales. European Journal of Social Sciences, 2012)
Our ambition is to point out that a fresh look at what is usualy considered to be Karl Polanyi’s magnum opus, The Great Transformation, opens some new prospects on its analytical. This interpretation qualifies some of the Hungarian author’s main critics, directed against his concept of desembeddedness. With this aim in mind, we re-interpret this debate in epistemological terms, i.e. the link between concepts and reality ; then we try to connect Karl Polanyi with the notion of performativity, which is today flourishing, above all within the field of economic sociology.
Keywords: Great Transformation, The (Book); Karl Polanyi; disembeddedness; great transformation; performativity; realism

Crise ? Vous avez dit : « Crise » ? - Naszályi, Philippe (Revue des Sciences de Gestion, 2012)
Crisis and institutional environment, crisis and organisational anticipations and crisis and consumer behaviour, just a few of the uses of the word « crisis » ; a word which, for over four years now, for the less perspicacious, and for over thirty years, for those who have been watching the bigger picture, has been the most appropriate word for this stage of development of the contemporary economic system. But exactly « what crisis are we talking about? ». That which is the result of a system, of an ideology which inhabits this system and of which the slightest of abilities was to try and present itself as unable to be exceeded, « by the end of the story ».' Yet, just as Max Weber stated, it seems that today's knowledge is still destined to be exceeded, particularly in the humanities, since society is constantly undergoing transformation. There is, therefore, no economic model which should not be discussed in order to be improved, or replaced. By delving into the ideal of Sismondi, today wrongfully forgotten, or in studying Karl Polanyi, we can gain much support for contemporary reflection which cannot continuously oppose Keynes, often summarised to the deficit of public policies and the « Chicago Boys » of which the action with Augusto Pinochet is truly symbolic of this « neo-liberalism» of American conservatives which is spreading across the globe, despite the crises which it has created. Crisis? Did you say: « Crisis' ? A question, and observation, but also in the manner of «great thinkers », solutions and alternatives which managers, in the widest sense of the term, « those who look after others and their businesses », provide through thirteen articles, collated into three thematic sections in this Spring edition which opens up new areas for reflection and action as « it is indeed time to put production before speculation, future investment before current satisfaction, sustainable employment before immediate profiteering ». (English)
Keywords: WEBER, Max, 1864-1920; consumer behavior; economic models; economic systems; humanities; institutional environment

La société contre le marché - Skornicki, Arnault (The Life of Ideas, 2012)
A propos de : Karl Polanyi, La Subsistance de l'homme. La place de l'économie dans l'histoire et dans la société, Flammarion
Keywords: capitalisme; commerce; marché